Quality Assurance Policy Implementation and Effective performance management in Higher Education Institutions in Developing Countries - Mwesigye, Adrian Rwekaza; Kibalirwandi, Moses Muhindo (ISAR Journal of Arts, Humanities and Social Sciences, 2024)
Effective performance management in higher education institutions requires institutions to administratively adapt and implement quality assurance policy. Quality assurance is an education reform policy aimed to enhance the continuous improvement of higher education quality. The policy was adapted in African states from European countries as it originated from Italy: Bologna process accord of 1999. The Bologna process accord was preceded by the Sorbonne Declaration of May 1998 meant to increase students' and employees' mobility across different political boundaries in providing solutions to quality education and solving the problem of unemployment. Educational reform policies are best evaluated on the anticipated outcomes as a testimony of internal and external stakeholders’ engagement in the system. The question of who are the stakeholders to effectively improve the performance of university and other tertiary education is the point of discussion. In this study, we accentuate the importance of human resource engagement in quality assurance policy implementation to enhance service delivery and product output in organisations like universities and other tertiary institutions. Empirical results show that effective performance management is achieved when staff participation is encouraged. It is empirically tested that employees contribute 68.5% success to policy implementation at the organisation level (Kibalirwandi, 2023). The anticipated mutual benefits that involve rewards, recognitions, promotions, increased revenue and change in standards of living for both employees and employers appear evident in national statistics of growth and development as a contribution from the national education system. Quality assurance in universities and other tertiary institutions is a key development indicator for UN-SDG Goal #4 as far as sustainable development goals (SDGs) that are discussed in the 2030 United Nations targets. Human resource management is an important factor of production in both developed and underdeveloped countries.
Keywords: Human resource management; Employees engagement; Rewards; Recognitions; System management; Effectiveness; Efficiency and Performance